Auto-morphism of Finite Dimensional Leibniz Algebras Dimension (2) & (3) - H A Wasi; Ahmed Hadi Hussein (Genius Journals, 2023)
Discussing low-dimensional algebraic auto-morphism principles and looking at some new data to back them up are the goals of this study. These concepts have been revised to simplify computation for Leibniz algebra auto-morphism. The importance of these freshly published methods for determining auto-morphism is then illustrated by a number of fascinating findings and relevant examples.
Keywords: Leibniz Algebras; Auto-morphism; Finite Dimensiona